Religion and the obligations of citizenship - Weithman, Paul J., 1959- (Cambridge University Press, 2002)
"In Religion and the Obligations of Citizenship, Paul J. Weithman asks whether citizens in a liberal democracy may base their votes and their public political arguments on their religious beliefs. Drawing on empirical studies of how religion actually functions in politics, he challenges the standard view that citizens who rely on religious reasons must be prepared to make good their arguments by appealing to reasons that are "accessible" to others. He contends that churches contribute to democracy by enriching political debate and by facilitating political participation, especially among the poor and minorities, and as a consequence, citizens acquire religiously based political views and diverse views of their own citizenship.